ALTERNATIVE APPROACHES TO THE USE OF TWO COMPONENT ANTIPLATELET THERAPY IN PATIENTS WITH ACUTE CORONARY SYNDROME: EVIDENCES, RECOMMENDATIONS AND REAL PRACTICE - S. R. Gilyarevskiy; V. A. Orlov; I. M. Kuz'mina; A. G. Larin (Рациональная фармакотерапия в кардиологии)
Alternative approaches to the use of two component antiplatelet therapy in patients with acute coronary syndrome are discussed. Reasons to the development and implementation of new, more powerful antiplatelet agents are considered. Besides the evidence base for the practical application of new antiplatelet agents is discussed, especially this for ticagrelor which is the first-line drug in acute coronary syndrome according to European clinical guidelines. Subjective limitations of ticagrelor use in clinical practice are discussed, as well as a basis for overcoming these limitations.